2006
DOI: 10.1111/j.1463-1326.2006.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding sitagliptin, a dipeptidyl peptidase‐4 inhibitor, to metformin on 24‐h glycaemic control and β‐cell function in patients with type 2 diabetes

Abstract: In this study, the addition of sitagliptin 50 mg b.i.d. to ongoing metformin therapy improved 24-h glycaemic control and beta-cell function, and was generally well tolerated in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 14 publications
(18 reference statements)
5
112
0
Order By: Relevance
“…The improved islet function by sitagliptin results in reduction of both fasting glucose and prandial glucose as revealed in different studies in subjects with type 2 diabetes. 25,36,48,49 In fact, the entire 24-hour glucose profile is reduced by sitagliptin, as is evident from a study examining addition of sitagliptin to ongoing metformin therapy compared to metformin treatment alone (Figure 2). …”
Section: Mechanisms Of Actionmentioning
confidence: 94%
See 2 more Smart Citations
“…The improved islet function by sitagliptin results in reduction of both fasting glucose and prandial glucose as revealed in different studies in subjects with type 2 diabetes. 25,36,48,49 In fact, the entire 24-hour glucose profile is reduced by sitagliptin, as is evident from a study examining addition of sitagliptin to ongoing metformin therapy compared to metformin treatment alone (Figure 2). …”
Section: Mechanisms Of Actionmentioning
confidence: 94%
“…[21][22][23] These actions reduce both fasting and prandial glucose levels and the 24-hour glucose profile, as has been shown for NVP-DPP728 and sitagliptin. 24,25 Rodent studies have also shown that DPP-4 inhibitors (vildagliptin and sitagliptin) increase islet mass and normalize islet cell topography in diabetes models in mice. 26,27 This would suggest that DPP-4 inhibition targets the important islet dysfunctions in type 2 diabetes.…”
Section: Incretin-based Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…50 Improved glycaemic control has been observed with regimens involving combinations of metformin and the GLP-1 analogues, exenatide [51][52][53][54][55][56][57][58] and liraglutide, 59,60 or the DPP-4 inhibitors, vildagliptin 61,62 or sitagliptin. 26,[63][64][65][66] The additive antihyperglycaemic efficacy of these combinations relates to different cellular modes of action of metformin compared with each of the other classes of agents.…”
Section: Metformin In Combinationmentioning
confidence: 99%
“…21 Patients had diabetes for an average duration of 6.6 years, with average initial HbA1c level of 7.7% and average fasting plasma glucose level of 8.4 mmol/L. In a long-term study on the effect of sitagliptin as add-on therapy to metformin in subjects with inadequate glycemic control, sitagliptin (100 mg once daily) was added to metformin (1.5 g daily) for 24 weeks.…”
Section: Randomized Clinical Trial Sitagliptin As Add-on Therapy To Mmentioning
confidence: 99%